The potential educational value of mobile augmented reality games: the case of EduPARK App - Pombo, Lúcia (2020)
New teaching methodologies are nowadays integrating mobile devices, augmented reality (AR), and game-based learning in educational contexts. The combination of these three elements is considered highly innovative, and it allows learning to move beyond traditional classroom environments to nature spaces that students can physically explore. The literature does not present many studies of this approach’s educational value. The purpose of the study is to present an illustrative case of a mobile AR game in order to analyse its educational value based on the users’ opinion, both teachers and students, and on logs of game results. Through a mixed method approach, the educational value scale was applied to 924 users after playing the EduPARK app in a Green City Park. Results revealed high educational value scores, especially among teachers and students of 2nd and 3rd Cycles of Basic Education (83.0 for both). Hence, this particular software seems to be more suitable for 10–15 years-old students who highlighted motivational features, such as treasure hunting, points gathering, the use of mobile devices in nature settings, and AR features to learn. This study empirically revealed that mobile AR games have educational value, so these specific game features might be useful for those who are interested in creating or using games supported by apps for educational purposes.